Major Tudor authors : a bio-bibliographical critical sourcebook - Hager, Alan, 1940- (Gale virtual reference library., 1997)
A guide to the rich and diverse literature of Tudor England. Includes entries for numerous authors who wrote between 1485 and 1603.